The hacker and the state cyber attacks and the new normal of geopolitics - Buchanan, Ben (Harvard University Press, 2020)
"The threat of cyberwar can feel like something out of a movie: nuclear codes hacked, powerplants melting down, immediate crisis. In reality, state-sponsored hacking looks nothing like this. It's covert, insidious, and constant. Ben Buchanan reveals the cyberwar that's already here, reshaping the global contest for geopolitical advantage."
Keywords: Information warfare; Geopolitik; Cyberattacke; Cyberterrorismus; Cyber intelligence (Computer security); Hacking / Political aspects; Cyberterrorism; Cyberspace operations (Military science); Cyberspace / Political aspects